ANALYSIS OF ERROR SOLUTION OF MATHEMATICS STORIES BASED ON WATSON CRITERIA - Santoso, Yolanda Olivia; Yunita, Alfi; Muslim, Audra Pramitha (Universitas Tanjungpura, 2022)
This research is motivated by the number of errors made by students in solving math problems. The purpose of this study was to determine the types of errors made by students in working on math problems based on Watson's criteria in class IX.8 and to determine the factors that caused students to make mistakes in doing math problems based on Watson's criteria in class IX.8. The research method used is descriptive method with a qualitative approach. The sampling technique used is purposive sampling technique. The sample in this study consisted of 32 students, for further research from the existing sample, namely 5 students according to the level of academic ability and certain considerations. The results of this study indicate that the types of errors made by students with high academic abilities are incorrect procedures and missing conclusions. The types of errors of moderate ability students are missing data, wrong procedures and missing conclusions. The types of errors made by students with low academic ability are inaccurate data, wrong procedures, missing data and missing conclusions. The cause of students making mistakes is that students do not understand the questions, students are confused in answering questions and forget to use the correct formula. So it can be said that the error in reading mathematical stories is in accordance with Watson's Criteria.